2005
DOI: 10.1108/02621710510584026
|View full text |Cite
|
Sign up to set email alerts
|

A gender‐based categorization for conflict resolution

Abstract: PurposeAs the workforce becomes increasingly diversified, it becomes increasingly important for managers to understand the conflict resolution attitudes brought to information systems (IS) by both men and women. This research was designed to investigate assumptions that may exist regarding the relationship between gender and conflict resolution. Specifically, the intent of this study was to compare the conflict resolution strategies of males and females majoring in IS in order to determine if gender‐based diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 40 publications
5
67
0
13
Order By: Relevance
“…This may be due to the fact that the wives gender role tendency to concern for others, role expectation and their tendency to take care of husbands. The data is in accordance with the findings of Brahman et al (2005) who claimed that men and women tend to endorse conflict handling strategies that complement gender role expectations in handling conflicts, women unlike men, favor accommodating strategies. Men prefer to be more collaborating and avoiding in their style of conflict handling which accords precisely with gender role expectations, as they are expected to remain cool and in control (Haferkamp, 1991).…”
Section: Gender and Tacticssupporting
confidence: 81%
“…This may be due to the fact that the wives gender role tendency to concern for others, role expectation and their tendency to take care of husbands. The data is in accordance with the findings of Brahman et al (2005) who claimed that men and women tend to endorse conflict handling strategies that complement gender role expectations in handling conflicts, women unlike men, favor accommodating strategies. Men prefer to be more collaborating and avoiding in their style of conflict handling which accords precisely with gender role expectations, as they are expected to remain cool and in control (Haferkamp, 1991).…”
Section: Gender and Tacticssupporting
confidence: 81%
“…According to Calhoun and Smith (1999), women are also more likely to rate themselves as friendly and trustworthy. Results of a study carried out by Brahnam et al (2005) indicate that women are more inclined to use a collaborative con ict resolution style and men tend to avoid con ict. Since cooperation is generally seen as more useful and avoidance more obstructing in the con ict resolution process, their study suggests that women may have more productive con ict resolution characteristics than men.…”
Section: Gender and Negotiation Behaviourmentioning
confidence: 99%
“…Integration style of conflict resolution is positively correlated to participants' satisfaction. Brahnam et al, (2005) have studied the relationship between gender and conflict resolution techniques used by a study of one hundred sixty-three Information Systems undergraduate students at a Midwest university in USA. They found that women use mostly collaborative style of conflict resolution and men avoid the conflict in information systems projects.…”
Section: Previous Literature On Conflict Managementmentioning
confidence: 99%